A Novel Approach to Enhance Efficiency and Productivity in Papua New Guinea Using an Automatic Coconut Punching Machine - Mohamed Aezeden (SHS Web of Conferences)
The world demand for coconut products is increasing, thus a need for efficient and cost effective processing solutions has arisen. Thus, we have developed an automatic coconut punching machine with key advanced technologies to revolutionize the coconut processing industry in Papua New Guinea. Automated punching not only improves efficiency but significantly improves productivity by 400% versus old manual methods and lowers labor costs. The aim of this machine is to accommodate for local and industrial production, so that it is flexible and can be used for different sized tools. This paper focuses on operational challenges of machine development and implementation phases including technical adjustments so that machine can function optimally. A comparison shows the superiority of the automated system compared to conventional methods in respect of speed, consistency and cost efficiency. Furthermore, experimental results also suggest that the machine is useful not only to increase productivity but also maintain the quality of punched coconuts at the level required by the industry and consumer expectation.The automated coconut punching machine is a predominant technological achievement in Papua New Guinea's coconut processing industry which could be adapted elsewhere to other areas of the world where coconuts are produced. This innovation addresses key challenges of the sector, reducing the manual labour and increasing output to spur sustainable development and increasing global competitiveness.